Unsatisfactory completeness of nurses' records in the medical records of users with tuberculosis - José Nildo de Barros Silva Júnior; Haline Costa dos Santos Guedes; Dilyane Cabral Januário; Ana Cristina de Oliveira e Silva; Pedro Fredemir Palha; Matheus Figueiredo Nogueira; Anne Jaquelyne Roque Barrêto (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to evaluate the completeness of nurses' records on the execution of the nursing process in assistance of tuberculosis patients at Primary Care. Methods: this was a retrospective documental study, with 190 records in Family Health Units of a city in the state of Paraíba. The data were analyzed according to descriptive statistics, Pareto Diagram, and trend analysis. Results: the overall mean incompleteness of records was 53.01% (DP=26.13). Therefore, the results presented very poor completeness classification related to nursing diagnosis (88.9%), nursing assessment (66.8%), data collection (60.5%), while nursing interventions were classified as regular (11.1%). The nursing diagnosis was the only variable with a decreasing trend of non-completeness. Conclusions: incompleteness of nurses' records in the medical records of users with tuberculosis. Evaluation strategies, permanent and continuing education are indispensable in the quality of nurses' documentation, directly implying the Systematization of Quality in Nursing Care.